EPIDEMIOLOGICAL CHARACTERISTIC OF HERPES SIMPLEX VIRUS TYPE 2 INFECTION AT A LARGE CENTER OF RUSSIAN ARCTIC ZONE - T. V. Balaeva; O. V. Samodova; A. L. Sannikov (Журнал инфектологии)
Globally, infection caused by herpes simplex virus type 2 (HSV-2) is one of the most prevalent sexually transmitted infections and the most frequent cause of the genital ulcer diseases. The information about HSV-2 epidemiology in Russia is insufficient. Aim of the study: to define the prevalence of HSV-2 among general adult population in Northwest Russia (Arkhangelsk).Material and methods. The study was a part of a large Norwegian-Russian project and has a population-based cross-sectional design. The agency on social researches recruited residents of Arkhangelsk using a quota sampling method. The ELISA method was used to test the blood samples on Ig G g2; kits of Vector Best (Novosibirsk, Russia) were used.Results. Altogether, 1243 participants provided the blood samples and fulfilled the questionnaire. Men represented 44% (543 persons) and women – 56 (700 persons), the mean age was 27,6±5,6 and 27,0±5,7 years respectively. Seroprevalence of HSV-2 in the sample was 18,8% (95% CI 16,8– 21,1), seroprevalence among women was in 2 times higher compared with men (24,0%, 95% CI 20,1–27,3 and 12,2%, 95% CI 9,7–15,2 respectively; p<0,001). The percentage of positive results increased with age in both men and women.Conclusion. According to our data seroprevalence of HSV-2 among young adults in Arkhangelsk was comparable with seroprevalence in some European countries with high figures and with USA. High prevalence of HSV-2 among females in reproductive age shows the potential of this infection in vertical transmission.